P2-S2.21 Traditional devadasi system under transition: boon or bane for HIV prevention programme?. (10th July 2011) - Gurav, K; Cooper, E; Junno, J; Stein, D; Chintada, D R; Doddamane, M; Moses, S
Abstract : Background: One of the key factors attributed to high prevalence of HIV in Northern Karnataka (in India) is socially accepted and widely practiced sex work. Girls from "Devadasi" community enter into sex work through socially accepted way of being dedicated to deity "Yellamma". Currently, the "Devadasi" system is under transition where, new dedications are not accepted by community leaders. As a result, the social organization of traditional sex work is changing. Methods: An exploratory research was undertaken in the district of Bagalkot, Karnataka. Ethnographic methods, including participant observation and Focus Group Discussions (FGDs) were used. FGDs were conducted with leaders, sex workers, peer educators, adolescent girls from "Devadasi" community and HIV service providers. Results: "Daiva" is a committee consisting of key leaders from "Devadasi" community. "Daiva" functions at the local (village) level and make decisions for the welfare of their community. The death of many young "Devadasi" sex workers due to AIDS was reported as a key factor for "Daiva" in stopping girls from entering sex work. Towards this end, "Daiva" has declared that the families who dedicate their daughters will be fined (RS 5000 to 20 000) and be outcasted. Although there seem to be a consensus to the decision of "Daiva", there are families who still want their daughters to start sex work. The fear of social and financial reprimand is placing new sex workers and their families in a marginalised and potentially illegal position within their village. Meanwhile, it is making new "Devadasi"? sex workers, conceal their identity and also avoid the HIV prevention services offered by peer educators of their own community at the door step. Conclusion: Changing social organization and conditions of "Devadasi" sex workers increases their intrinsic risk and vulnerability to HIV. Therefore it is important to address the structural changes occurring within the "Devadasi" community and also create an environment for new sex workers to freely access HIV prevention and care services. An innovative intervention model that could negotiate between objectives of "Daiva" and needs of sex workers is required."